Combining PARP and DNA-PK Inhibitors With Irradiation Inhibits HPV-Negative Head and Neck Cancer Squamous Carcinoma Growth - Zeng, Ling; Boggs, Drexell Hunter; Xing, Chuan; Zhang, Zhuo; Anderson, Joshua C.; Wajapeyee, Narendra; Veale, Chris; Bredel, Markus; Shi, Lewis Z.; Bonner, James A.; Willey, Christopher D.; Yang, Eddy S. (Frontiers in Genetics, 2020)
Novel targeted agents to inhibit DNA repair pathways to sensitize tumors to irradiation (IR) are being investigated as an alternative to chemoradiation for locally-advanced HPV negative head and neck squamous cell carcinoma (HNSCC). Two well-characterized targets that when inhibited exhibit potent IR sensitization are PARP1 and DNA-PKcs. However, their cooperation in sensitizing Human Papilloma Virus negative (HPV negative) HNSCC to IR remains to be explored, given PARP1 and DNA-PkCS bind to unresected stalled DNA replication forks and cooperate to recruit XRCC1 to facilitate DSB repair. Here, we showed that the combination of the DNA-PK inhibitor NU7441 and the PARP inhibitor olaparib significantly decreased proliferation (61-78%) compared to no reduction with either agent alone (p<0.001) in both SCC1 and SCC6 cell lines. Adding IR to the combination further decreased cell proliferation (91-92%, p<0.001) in SCC1 and SCC6. Similar results were observed using long-term colony formation assays (dose enhancement ratio [DER] 2.3 – 3.2 at 4Gy, p<0.05). Reduced cell survival was attributed to increased apoptosis and G2/M cell cycle arrest. Kinomic analysis using tyrosine (PTK) and Serine/Threonine (STK) arrays revealed that combination treatment resulted in most potent inhibition of kinases involved in the CDK and ERK pathways, compared to either agent alone. In vivo, a significant delay of tumor growth was observed in UM-SCC1 xenografts receiving IR with olaparib and/or NU7441, which was similar to the cisplatin-IR group. Both regimens were less toxic than cisplatin-IR as assessed by loss of mouse body weight. Taken together, these results demonstrate that the combination of NU7441 and olaparib with IR enhances HPV negative HNSCC inhibition in both cell culture and in mice, suggesting a potential innovative combination for effectively treating patients with HPV negative HNSCC.